Continuous vocational education and training and new technologies : on the importance of educational level and technology in the workplace - Stöckl, Andreas [Verfasser]; Struck, Olaf [Verfasser] (My University, 2025)
“Continuing vocational education and training (CVET) can support technical and digital developments. At the same time, company-based training increases employability in the face of technical rationalization. Multiple studies show that the highly qualified undertake further training more often than the less qualified. This increases their educational and employment inequality. However, it is unclear whether this general finding also applies to participation in CVET when new technologies are introduced in companies. Companies could have an interest in the deployment of all their employees. The introduction of new technologies in a company context could lead to people with professional qualifications as well as those with higher qualifications taking part in CVET. Using the Linked Personnel Panel (LPP) and the IAB Establishment Panel, we investigate whether the participation of employees with university-level education and upper secondary vocational education differ if the participation in CVET is attributed directly to the introduction of technology in the workplace. The outcomes show that the more highly qualified use forms of self-study more frequently. However, there are only marginal differences between highly qualified and professionally qualified employees when it comes to the use of courses as part of in-house training.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; G 2.2.1 Technologisierung; 370; Weiterbildungsforschung; Betriebliche Weiterbildung; Digitalisierung; Weiterbildungsbeteiligung; Einflussfaktor; Qualifikationsniveau; Facharbeiter; Akademiker